Active Coated Films to Decrease Browning of Minimally Processed Banana Fruit. Issue 1 (21st October 2022) - Apicella, Annalisa; Carlucci, Elisa; Leneveu‐Jenvrin, Charlène; Remize, Fabienne; Scarfato, Paola
Abstract: Minimally processed fruit presents a short shelf‐life because of cellular endogenous metabolism or microbial development. Fruit browning mostly results from phenolic compound oxidation. Banana ( Musa acuminata Cavendish) cuts are particularly prone to enzymatic browning, resulting in unattractive color and modifications of aroma. In this study, the effect of two different eco‐sustainable packaging films on minimally processed banana is investigated. The films differ by the substrate, either polyethylene terephthalate (PET) or a fully biodegradable mix of polylactic acid (PLA) and polybuthylene adipate terephtalate (PBAT). They are coated with an amorphous PLA layer containing as antioxidant an active agent deriving from olive processing wastes. Minimally processed banana slices are prepared, packed, and stored at 4°C. Microbiological quality, color, pH, firmness, and polyphenol oxidase activity are evaluated during storage. The PET films show a better efficacy to limit browning, mainly due to the higher oxygen barrier properties compare to the PLA/PBAT. Best results are obtained with PET films with 5% of active phase.